VALIDITAS MEDIA INTERAKTIF KOBAR (KOSAKATA BARU) BERBASIS ARTICULATE STORYLINE UNTUK PEMBELAJARAN MEMBACA PESERTA DIDIK KELAS II SEKOLAH DASAR - Anjani, Nelfira; Sukma, Elfia; Habibi, M.; Adrias, Adrias (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mastery of vocabulary is among the crucial aspects toward supporting the growth of elementary school students’ reading skills. However, in practice, vocabulary learning in second grade of elementary school is still dominated by traditional approaches like using textbooks and lectures, which are less able to attract students’ interest and learning motivation. This condition causes students to experience difficulties in understanding new vocabulary and comprehending the content of reading texts. Therefore, learning innovation is required by utilizing interactive digital media that can produce more captivating educational opportunities. This study intends to produce the Kobar (New Vocabulary) interactive media based on Articulate Storyline for reading instruction of second-grade elementary school students and to analyze its validity level. The ADDIE instructional design model, which was restricted within the phases of analysis, design, and development, was applied in this study’s Research and Development (R&D) process. Observation, interviews, student needs questionnaires, and validation questionnaires, validated by three experts in material, language, and media, were used to collect data. As indicated by the results, the Kobar media received a very valid validity score, including 95% from the material expert, 95% from the language expert, and 100% from the media expert, resulting in an overall average validity of 96.87%. Therefore, the Kobar interactive media is thought to be practical for usage as a teaching tool to enhance second-grade elementary school pupils' vocabulary acquisition and reading comprehension.